math.com
Home    |    Teacher    |    Parents    |    Glossary    |    About Us
Homework Help Practice Ask An Expert Calculators & Tools Games Store
Email this page to a friend Email this page to a friend
Resources
· Cool Tools
· Formulas & Tables
· References
· Test Preparation
· Study Tips
· Wonders of Math
 
Search
Custom Search



Math Jobs


  
 
Proof: Integral csch(x)
(Math | Calculus | Integrals | Table Of | csch x)
 
Discussion of
(integral) csch x dx = ln | tanh(x/2) | + C.

1. Proof

    Strategy: Use definition of csch; use algebra; use substitution; use partial fractions.
    csch x =

    sinh x
    =

    ex - e-x
     
    (integral) csch x dx = (integral)
    2 
    ex - ex
    dx
    multiply numerator and denominator by ex
    (integral) 

    (ex - ex)
    (ex
    (ex)
    dx
     
     (integral)
    2 e
    (e2x - 1)
    dx
    set
      u = ex
    then we find
      du = ex dx

    substitute du = ex dx, u = ex
     
    (integral)
    2 du 
    u2 - 1
    the denominator is factorable; use partial fractions
    (integral)
    2 du
    (u + 1)(u - 1)
    (integral)

    u + 1
    +

    u - 1
     du

       

      (u + 1)(u - 1)
      =

      u + 1
      +

      u - 1
      multiply both sides by (u + 1)(u - 1)

      2 = A(u - 1) + B(u + 1)
      2 = Au - A + Bu + B
      2 + 0u = (-A + B) + (A + B)u

      therefore
      -A + B = 2
       A + B = 0
      ------------- (add)
             2B = 2
               B = 1
      A + 1 = 0
      A = -1

     
    (integral)
    -1 du 
    u + 1
    (integral)
    1 du 
    u - 1
    set v = u + 1, w = u - 1
    then we find dv = du, dw = du
    substitute
    = - (integral)
    dv 
    v
    (integral)
    dw 
    w
    solve both integrals

    = - ln |v| + ln |w| + C

    substitute back v = u + 1, w = u - 1

    = - ln |u + 1| + ln | u - 1| + C
    = ln |
    u - 1 
    u + 1
    | + C
    substitute back u = ex
    = ln |
    ex - 1 
    ex + 1
    | + C
    multiply the numerator and denominator by ex/2
    = ln |
    (ex - 1) ex/2 
    (ex + 1) ex/2
    | + C = ln | ex/2 - ex/2 
    ex/2 + ex/2
    | + C

    recall that

      tanh x =
      ex - ex
      ex + ex
    therefore
    = ln | tanh(x/2) | + C
    Q.E.D.
  
 
  

 
Contact us | Advertising & Sponsorship | Partnership | Link to us

© 2000-2005 Math.com. All rights reserved.     Legal Notices.     Please read our Privacy Policy.